2005
DOI: 10.1007/s10549-005-9039-1
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors for patients with liver metastases from breast cancer

Abstract: Consideration of prognostic implications of the described parameters may help to find the most appropriate treatment for patients with liver metastases from breast cancer. The possibility of local therapeutic interventions should be considered in a defined subgroup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 29 publications
0
39
1
Order By: Relevance
“…Although toxicity data in patients aged $65 years have not been reported for the MPACT study to date, a separate analysis of dosing in the study revealed that the percentage of dose reductions in the nabpaclitaxel plus gemcitabine arm was similar regardless of age ($65 vs. ,65 years) [11]. Taken together, the findings of this analysis are particularly relevant considering that patients with these characteristics (e.g., advanced age, poor performance status, presence of liver metastasis, or more than three metastatic sites) tend to have especially poor survival outcomes [12][13][14][15].…”
Section: Wwwtheoncologistcom ©Alphamed Press 2015mentioning
confidence: 98%
“…Although toxicity data in patients aged $65 years have not been reported for the MPACT study to date, a separate analysis of dosing in the study revealed that the percentage of dose reductions in the nabpaclitaxel plus gemcitabine arm was similar regardless of age ($65 vs. ,65 years) [11]. Taken together, the findings of this analysis are particularly relevant considering that patients with these characteristics (e.g., advanced age, poor performance status, presence of liver metastasis, or more than three metastatic sites) tend to have especially poor survival outcomes [12][13][14][15].…”
Section: Wwwtheoncologistcom ©Alphamed Press 2015mentioning
confidence: 98%
“…Gastric cancers also commonly metastasize to the liver (7). Circulating cells from other primary malignancies, such as melanoma, breast or neuroendocrine tumors (8)(9)(10), also adhere, establish and develop in the liver, giving rise to metastases, although this is less common.…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer cells preferentially metastasize to specific organs and tissues, with the liver representing the third most frequent site following bone and lung (Clark et al, 1987;Insa et al, 1999). Breast cancer patients with liver metastases display a poor prognosis, with median survival times between 14 and 20 months and 5-year survival rates that reach only 5.5-8.5% (Pentheroudakis et al, 2005;Eichbaum et al, 2006). However, little is known about the molecular mechanisms governing the spread and growth of breast cancer cells in the liver.…”
Section: Introductionmentioning
confidence: 99%